Crossdressing Dansō: Negotiating between Stereotypical Femininity and Self-expression in Patriarchal Japan. Issue 1 (1st March 2019) - Fanasca, Marta
Abstract : In this article, I focus on the childhood and adolescent life experiences of dansō (female-to-male crossdressers) who work as escorts in contemporary Japan, and on the process that led to their presentation of self as gendered masculine in their private and working lives. During their childhood and adolescence, dansō have to negotiate their identity and self-presentation to adhere to the gendered pressures of Japanese society. Through an analysis of interviews undertaken with 14 dansō informants, I explore dansō's construction of a male identity before adulthood, highlighting the societal impositions they experienced and the coping strategies to which they resorted in order to create and maintain a space in which to express their queer selves.